2022
DOI: 10.1155/2022/1704948
|View full text |Cite|
|
Sign up to set email alerts
|

A New Method for Early Screening of Gastric Cancer (G17 and CA724 Dual-Labeled Time-Resolved Fluorescence Immunoassay)

Abstract: Gastric carcinoma (GC) is one of the most common malignancies in the world with the great early screening challenges. The study is aimed at establishing a new detection method for early screening GC using time-resolved fluorescence immunoassay (TRFIA) via quantitative detection of gastrin-17 (G-17) and carbohydrate antigen 724 (CA724) in serum. Time-resolved analyzer measured the fluorescence intensity. The standards of G-17/CA724 were used for drawing the standard curve, which is used to calculate the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%